Do Enhanced Collective Action Clauses Affect Sovereign Borrowing Costs? - Chung, Kay (IMF Working Papers; Working Paper, 2020)
This paper analyzes the effects of including collective action clauses (CACs) and enhanced CACs in international (nondomestic law-governed) sovereign bonds on sovereigns' borrowing costs, using secondary-market bond yield spreads. Our findings indicate that inclusion of enhanced CACs, introduced in August 2014, is associated with lower borrowing costs for both noninvestment-grade and investment-grade issuers. These results suggest that market participants do not associate the use of CACs and enhanced CACs with borrowers' moral hazard, but instead consider their implied benefits of an orderly and efficient debt resolution process in case of restructuring.